2015
DOI: 10.1162/jocn_a_00845
|View full text |Cite
|
Sign up to set email alerts
|

Preparatory Activity in Posterior Temporal Cortex Causally Contributes to Object Detection in Scenes

Abstract: Theories of visual selective attention propose that top-down preparatory attention signals mediate the selection of task-relevant information in cluttered scenes. Neuroimaging and electrophysiology studies have provided correlative evidence for this hypothesis, finding increased activity in target-selective neural populations in visual cortex in the period between a search cue and target onset. In this study, we used online TMS to test whether preparatory neural activity in visual cortex is causally involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…However, automatic priming (or spreading of activation) does not fully explain the spatial and content‐based preparatory attention findings reviewed here. For example, studies have shown that sustained preparatory activity in the visual cortex is only observed when the cue is actively maintained in preparation for a subsequent visual task and that preparatory activity in response to a symbolic cue reflects the specific requirements of the subsequent detection task . These and other findings are not in line with automatic priming accounts.…”
Section: How Does Preparatory Activity Facilitate Perception?mentioning
confidence: 94%
See 1 more Smart Citation
“…However, automatic priming (or spreading of activation) does not fully explain the spatial and content‐based preparatory attention findings reviewed here. For example, studies have shown that sustained preparatory activity in the visual cortex is only observed when the cue is actively maintained in preparation for a subsequent visual task and that preparatory activity in response to a symbolic cue reflects the specific requirements of the subsequent detection task . These and other findings are not in line with automatic priming accounts.…”
Section: How Does Preparatory Activity Facilitate Perception?mentioning
confidence: 94%
“…TMS has also provided evidence for causal involvement of content‐based preparatory activity in attentional selection. In two experiments, Reeder et al . followed up on an earlier fMRI study that localized preparatory activity for naturalistic visual search to a region in the posterior temporal cortex (pTC) .…”
Section: Neural Evidence For Preparatory Activity In the Visual Cortexmentioning
confidence: 99%
“…In the present study, the wide range of different basic-level categories in each superordinate category would have rendered top-down preparation for diagnostic object parts less effective, and the inclusion of incongruent foreground-background scenes precluded preparation for low-level features (e.g., colors). To determine the content of preparatory templates for superordinate categories, future studies may use attentional capture paradigms to test to which stimulus features observers automatically orient while preparing to detect animals or vehicles (Reeder & Peelen, 2013; Reeder et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Patterns of neural responses in object-sensitive cortex to images of natural scenes are dominated by task-relevant objects, while responses to task-irrelevant objects are weaker (Peelen & Kastner, 2011; Peelen et al, 2009) or even suppressed (Seidl, Peelen, & Kastner, 2012). This category-specific modulation of neural activity occurs early in time, modulating the initial categorical representation of the scene (Kaiser, Oosterhof, & Peelen, 2016) and is related to preparatory cue-related activity, prior to the presentation of the scene (Peelen & Kastner 2011; Reeder, Perini, & Peelen, 2015; Soon, Namburi, & Chee, 2013). These preparatory signals may constitute the neural substrate of category-diagnostic templates that bias the processing of scenes in favor of the task-relevant category, providing the neural basis for the beneficial effect of category-based attention observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recent evidence suggests lateral prefrontal cortex does code content-specific information during a delay 22 , consistent with the current findings. Finally, posterior temporal cortex has previously been found to represent the contents of complex objects in the target template 15, 53 , as well as showing high-level feature and shape-selective processing during object viewing 5456 and conjunction processing 57 . The current results provide evidence for a role of posterior temporal cortex in representing task relevant feature dimensions.…”
Section: Discussionmentioning
confidence: 99%